Aplikasi Penginderaan Jauh dan SIG dalam Penilaian Potensi Erosi Permukaan secara Kualitatif di Daerah Tangkapan Waduk Kedung Ombo - Miardini, Arina; Harjadi, Beny (Forum Geografi, 2011)
The purpose of this study was to determine the potential erosion qualitatively by using SES by using Remote Sensing and Geographic Information Systems in Kedung Omboâs catchment area so it can be determined which areas of priority should be conserved. The method used is qualitatively analyses through SES method (Soil Erosion Status).) Which is calculated based on five parameters are: slope direction (aspect), slope (slope gradient), the density of the river (drainage density), soil type (Soil types), and land use (landuse/landcover). The result shows that DTW Kedung Ombo has three classes of erosion, which is very low, low and medium. Amounted to 41179.08 ha or 71.31% of the total DTW Kedung Ombo erosion potential is still relatively mild, 13956.01 ha (24.17%), erosion potential is very low and 2608.95 ha (4:52%) were classified as potential erosion.